2002
DOI: 10.1536/jhj.43.487
|View full text |Cite
|
Sign up to set email alerts
|

QT Dispersion in Patients with Polycystic Ovary Syndrome.

Abstract: SUMMARYCardiac risk factors are observed more frequently in patients with polycystic ovary syndrome (PCOS). On the other hand, increased QT dispersion, which is a risk factor for cardiac arrhythmias and sudden death, has not been investigated in this syndrome. In this study, we evaluated QT dispersion in PCOS patients without overt heart disease. Thirtysix consecutive women with PCOS (mean age 24±5 years) and 36 healthy women of similar ages (mean age 24±4 years) participated in this study. PCOS was diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
9
2
Order By: Relevance
“…Although the QT interval and QT dispersion were suggested to play a role in cardiac-related mortality, we found no differences in QT dispersion or QTc dispersion between patients with and without PCOS, which was similar to findings of previous studies [14,15]. In contrast, in this study, we found that the QRS duration was prolonged in the PCOS group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the QT interval and QT dispersion were suggested to play a role in cardiac-related mortality, we found no differences in QT dispersion or QTc dispersion between patients with and without PCOS, which was similar to findings of previous studies [14,15]. In contrast, in this study, we found that the QRS duration was prolonged in the PCOS group.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies showed that PCOS patients had similar QT interval and QT dispersion compared to healthy women [14,15]. Interestingly, Orio et al [14] showed that PCOS has a tendency to prolong the QRS duration.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that a negative correlation between serum testosterone level and QT duration, and shorter minimum QT durations in patients with PCOS (7). Accordingly, a study suggested that QT dispersion did not differ in patients and control subjects, however, relationship between sex hormone levels and QT durations was not reported in this study (8). It was known that change in hormonal values is related to menstrual cycle.…”
Section: Introductioncontrasting
confidence: 59%
“…Alparslan et al (8) reported that QT dispersion did not differ between women with PCOS and controls. There was no information about the levels of estradiol in their study.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies dealing with the QT dispersion and duration in patients with PCOS suggest that the risk of ventricular arrhythmias is not increased in these patients and these results were attributed to elevated testosterone levels (10, 11). On the other hand, PCOS was associated with ECG markers of the inhomogeneous atrial conduction, which has a predictive value for the atrial fibrillation (AF) (12).…”
Section: Introductionmentioning
confidence: 87%